Economic Value of Florida Water Resources: Value Derived by Tourists and Recreationists from Freshwater-Based Recreation - Tatiana Borisova; Tara Wade; Xiang Bi; Kurt Oehlbeck; Kelly A. Grogan (EDIS)
This 8-page fact sheet written by Tatiana Borisova, Tara Wade, Xiang Bi, Kurt Oehlbeck, and Kelly Grogan and published by the UF/IFAS Food and Resource Economics Department is part 3 of the series “Economic Value of Florida Water Resources.” It uses Florida-based economic studies to provide natural resource professionals and interested citizens with information regarding the value of water-based tourism and recreation in Florida. http://edis.ifas.ufl.edu/fe1067